Chronic kidney disease is a main confounding factor for 25-vitamin D measurement - Machado,Hanna Karla Andrade Guapyassú (2020)
Abstract Background: Current guidelines recommend assessment of 25-vitamin D status in patients with chronic kidney disease (CKD). Although significant differences among assays have been described, the impact of CKD on this variability has never been tested. Methods: We tested the variability between two 25-vitamin D assays in patients with CKD (eGFR < 60 mL/min/1.73m2) who had consecutive 25-vitamin D measurements in 2015 (Assay 1 - Diasorin LIASON 25 TOTAL - D assay®) and 2016 (Assay 2 - Beckman Coulter Unicel Xl 800®). The cohort consisted of 791 adult patients (122 with normal renal function and 669 with CKD - 33, 30, and 37% in stages 3, 4, and 5 on dialysis, respectively). Results: Levels of 25-vitamin D were lower and the prevalence of hypovitaminosis D using assay 1 was higher than using assay 2 in patients with CKD, regardless of similar levels of calcium, phosphate, and parathyroid hormone. As kidney function decreased, the percentage of disagreement between the assays increased. Conclusion: There is a noteworthy variability between assays in patients with CKD such that the diagnosis of hypovitaminosis D is modified. The mechanism behind this result is still unclear and might be due to a possible interference in the analytical process. However, the clinical significance is unquestionable, as the supplementation of vitamin D can be erroneously prescribed to these patients.